Effects of gas occurrence pattern on distribution and morphology characteristics of gas hydrates in porous media - Kou, Xuan; Li, Xiao-Sen; Wang, Yi; Liu, Jian-Wu; Chen, Zhao-Yang (Energy, 2021)
Natural gas hydrates have attracted much attention in recent years. It is important to investigate the effects of gas occurrence pattern on hydrate growth habits since distribution and morphology characteristics of gas hydrates have significant effects on physical properties of hydrate-bearing reservoirs. In this work, the differences in distribution and morphology properties of gas hydrates under two gas occurrence patterns have been analyzed via the X-ray computed tomography for the first time. Experimental results reveal direct correlations between the hydrate growth habit and the gas occurrence pattern. In the presence of free gas, grain-attaching hydrates are formed at the arc-shaped contact surface of gas and water, and mass transfer at the gas-water interface is the key controlling factor in hydrate formation process. In the presence of dissolved gas, dispersed and dendritic hydrates are formed in liquid phase as the result of gas solubility change, and gas diffusion is the crucial factor that influences the growth habit and morphology of gas hydrates during hydrate formation from dissolved gas. Besides, the maximum saturation of dendritic hydrates formed from dissolved gas is limited by the gas solubility. These conclusions are valuable in the improvement of prediction accuracy of gas production from hydrate-bearing sediments. (c) 2021 Elsevier Ltd. All rights reserved.